2017
DOI: 10.1111/apa.14162
|View full text |Cite
|
Sign up to set email alerts
|

Women who had positive relationships with their own mothers reported good attachments to their first child before and after birth

Abstract: We found that women who had positive relationships with their own mothers also had positive attachments to their unborn babies and in the period immediately after birth. Our findings supported Bowlby's attachment intergenerational transmission theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
2
18
0
1
Order By: Relevance
“…In reference to a woman's relationship with her parents, this result is convergent with previous studies that have found that the bond quality to mother significantly influences a woman's well-being during pregnancy and after delivery, considerably reducing the risk to develop a PPD condition (64). Tani et al (65, 66) have shown that the security of attachment to mother affects the quality of prenatal attachment and the consequent ability of the new mother to be sensitive to her newborn's needs, promoting spontaneous caregiving and attachment behavior. Maternal perceived support could also be considered a relevant protector factor: women who reported a high level of maternal social support showed a lower level of PPD symptomatology after labor (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In reference to a woman's relationship with her parents, this result is convergent with previous studies that have found that the bond quality to mother significantly influences a woman's well-being during pregnancy and after delivery, considerably reducing the risk to develop a PPD condition (64). Tani et al (65, 66) have shown that the security of attachment to mother affects the quality of prenatal attachment and the consequent ability of the new mother to be sensitive to her newborn's needs, promoting spontaneous caregiving and attachment behavior. Maternal perceived support could also be considered a relevant protector factor: women who reported a high level of maternal social support showed a lower level of PPD symptomatology after labor (31).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive literature has shown that women who felt more affection toward their unborn children have more compliance with health practices during pregnancy (71, 72), present less clinical complications during delivery, and show less difficulty, more confidence and better adjustment in assuming the new parenting role (73). Moreover, it has been found that prenatal attachment to the fetus plays a positive and significant role in promoting more adequate mother-child interactions (61) and spontaneous caregiving and attachment behavior after childbirth (65). Therefore, it is not surprising that the mother's prenatal attachment to child could represent a key element to improving the health of the mother and child, the outcome being a significant protective factor to prevent PPD onset.…”
Section: Discussionmentioning
confidence: 99%
“…Variables with some indications of a negative relationship with maternal-fetal bonding included substance abuse [19], anxiety [19], maternal age [18], being married [18], and experience with motherhood [18]. Other studies have shown a positive association between the quality of the relationship with one’s own mother in childhood and bonding to the fetus during pregnancy [20, 21]. In addition, pregnant women’s attachment style in romantic relationships relates to maternal-fetal bonding [2224].…”
Section: Introductionmentioning
confidence: 99%
“…Childhood experiences have a major impact on a person’s experience of parenthood and on adult attachment style (a facet of personality, shaped by early life experience, that structures adult interpersonal relationships) 909192. The quality of a woman’s relationships with her own parents is a known risk factor for mood disruption in the perinatal period9394; in one study of 88 women who completed a structured diagnostic interview in the third trimester, women who recalled maternal “affectionless control” were seven times more likely to be diagnosed as having postpartum depression (odds ratio 6.8, 1.80 to 25.37; P<0.005) 93…”
Section: Personalized Treatment For Specific Clinical Characteristicsmentioning
confidence: 99%